2016
DOI: 10.17344/acsi.2016.2242
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of L-Aspartic Acid with Aqueous Solution of 1,2-Propanediol at Different Temperatures: A Volumetric, Compressibility and Viscometric Approach

Abstract: The volumetric, acoustic and viscometric methods are used for investigating the interactions of L-aspartic acid (Asp) in aqueous solution of 1,2-propanediol (PD) over a temperature of (298.15, 303.15 and 308.15) K at atmospheric pressure. Using the experimental results, the apparent molar volume, V φ , limiting apparent molar volume, V 0 φ , the slope, S v , and partial molar volume of transfer, V 0 φ,tr, have been calculated from density data. The apparent molar isentropic compressibility, K φ , s , limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…On the other hand, the apparent molar volume increases with the increase of molality. Hedaoo et al, reported that the increased apparent molal compressibility was found to decrease with the creased concentrations of the amino acids in indicating a weak electrostatic force in the ionic environment leading to the electrostatic salvation of ions [10 The hydrophilic interaction leads to the negative values of molal ] editor@iaeme.com compressibility and apparent molar volume for both the amino acids L-leucine and L-glutamine [11]. The temperature has a very affective role on both these physical characteristics of the amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the apparent molar volume increases with the increase of molality. Hedaoo et al, reported that the increased apparent molal compressibility was found to decrease with the creased concentrations of the amino acids in indicating a weak electrostatic force in the ionic environment leading to the electrostatic salvation of ions [10 The hydrophilic interaction leads to the negative values of molal ] editor@iaeme.com compressibility and apparent molar volume for both the amino acids L-leucine and L-glutamine [11]. The temperature has a very affective role on both these physical characteristics of the amino acids.…”
Section: Resultsmentioning
confidence: 99%